2011
DOI: 10.1002/hed.21819
|View full text |Cite
|
Sign up to set email alerts
|

Association between severity of dysphagia and survival in patients with head and neck cancer

Abstract: Background This study examined risk factors for dysphagia, a common and serious condition in patients with head and neck cancer, and the association between severity of dysphagia and survival. Methods Chart reviews were performed on patients diagnosed with head and neck cancer between January 2001 and April 2003, who had dysphagia diagnoses or swallowing evaluations. Regression analyses determined factors associated with dysphagia and the association between observed survival and severity of dysphagia. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 43 publications
6
80
0
1
Order By: Relevance
“…The evaluation of severe dysphagia as a late complication of radiotherapy in patients surviving longer than five years was performed by Hutcheson et al The total dose of radiotherapy impacted the occurrence of late dysphagia; it was observed more frequently in patients with a total dose of 70 Gy or higher [26]. Many authors have observed positive effects from proactive swallowing therapy, which were observed not just following the treatment but also 3-6 months after the completion of chemoradiotherapy and 9-12 months after treatment [27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of severe dysphagia as a late complication of radiotherapy in patients surviving longer than five years was performed by Hutcheson et al The total dose of radiotherapy impacted the occurrence of late dysphagia; it was observed more frequently in patients with a total dose of 70 Gy or higher [26]. Many authors have observed positive effects from proactive swallowing therapy, which were observed not just following the treatment but also 3-6 months after the completion of chemoradiotherapy and 9-12 months after treatment [27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…(1)(2)(3)(4)(5)(6) In addition, there are consequences on the physical and mental condition of patients and it reduces their quality of life (QoL). (7,8) Patients with oral and oropharyngeal cancer are usually treated with surgery, radiotherapy (RT), and chemotherapy (ChT), administered alone or in combination.…”
Section: Introductionmentioning
confidence: 99%
“…(2)(3)(4)(5)(6)9) The main post-radiotherapy sequelae are mucositis, xerostomia, dysgeusia, hoarseness, fibrosis and osteonecrosis. (1,2) Difficulties with speech, mastication and swallowing are also produced. (1,(3)(4)(5)(6) Chemotherapeutic agents for head and neck cancer (HNC) can impact the ability of patients to swallow thus causing nutritional problems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations